Designing Woodleigh School: educator and architects in context. Issue 2 (30th September 2014) - Goad, Philip
Abstract : Purpose: – The purpose of this paper is to examine the professional context of the educator and architects who designed and conceived Woodleigh School in Baxter, Victoria, Australia (1974-1979) and to identify common design threads in a series of schools designed by Daryl Jackson and Evan Walker in the 1970s. Design/methodology/approach: – The research was derived from academic and professional publications, film footage, interviews, archival searches and site visits. Standard analytical methods in architectural research are employed, including formal, planning and morphological analysis, to read building designs for meaning and intent. Books, people and buildings were examined to piece together the design "biography" of Woodleigh School, the identification of which forms the basis of the paper's argument. Findings: – Themes of loose fit, indeterminate planning, coupled with concepts of classroom as house, and school as town, and engagement with a landscape environment are drawn together under principal Michael Norman's favoured phrase that adolescents might experience "a slice of life", preparing them for broader engagement with a world and a community outside school. The themes reflect changing aspirations for teenage education in the 1970s, indicating a free and experimental approach to the design of the school environment. Originality/value: – The paper considers, for the first time, the interconnected role of educator and architect as key protagonists in envisioning connections between space and pedagogy in the 1970s alternative school.